2015
DOI: 10.1515/biol-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Composition and herbicidal effect of Heracleum sosnowskyi essential oil

Abstract: Plants of Heracleum sosnowskyi Manden. are rich in essential oil which might be of herbicidal potential. In this study, we examined 1) the content and chemical composition of H. sosnowskyi essential oil (EO) distilled from seeds and 2) the herbicidal effect of EO in a bioassay against germination of maize and five weed species. As a result, a 5.1% EO yield was obtained from the seeds of H. sosnowskyi. We identified sixty-two compounds of EO that constituted 96% of the total oil. Aliphatic esters were the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…No significant differences were found in the chemical composition of the examined seed samples of Heracleum sosnowskyi and Heracleum mantegazzianum (Apiaceae), which confirms the suggestions that the species can be closely related [7]. The study useful for comparison of our results tested allopathic effect of EO isolated from H. sosnowskyi seeds on two dicots and four monocot species [24]. Different susceptibilities to H. sosnowskyi EO was evaluated in seeds germination as well as in radical length.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…No significant differences were found in the chemical composition of the examined seed samples of Heracleum sosnowskyi and Heracleum mantegazzianum (Apiaceae), which confirms the suggestions that the species can be closely related [7]. The study useful for comparison of our results tested allopathic effect of EO isolated from H. sosnowskyi seeds on two dicots and four monocot species [24]. Different susceptibilities to H. sosnowskyi EO was evaluated in seeds germination as well as in radical length.…”
Section: Discussionsupporting
confidence: 80%
“…Dominated components in EO identified in giant hogweed from Russia were octyl butyrate (32.0%), octyl acetate (18.0%) and hexyl butyrate (9.2%) [23]. Similar composition of seed EO as in H. mantegazzianum was noted in H. sosnowskyi [24]. Chemical composition of H. mategazzianum as well as H. sosnowskyi seed EOs that contained mainly octanol and hexanol esters of acetic acid, butyric and isobutyric acids differ from most of the evaluated EOs, in which terpenes dominate.…”
Section: Discussionmentioning
confidence: 98%
“…The plant has great potential in the pharmaceutical industry [13], [16]- [18], [21], [23]. One research is available on the material from the hogweed [13], but there is a potential for use in agriculture as a fertilizer [38] and antifungal agent [13], [20], [22], [38]. All parts of H. sosnowskyi plant can be used to produce products.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical compounds found in invasive plants, including Sosnowskyi’s hogweed ( H. sosnowskyi ), are harmful to human health, affect soil and alter the overall ecosystem of the area. H. sosnowskyi are rich in essential oils that contain mostly aliphatic esters, with the organic compound octal acetate or octyl ethanoate (molecular formula C 10 H 20 O 2 ) as the main constituent [ 20 ]. The substances present in these essential oils have strong, biologically active potential [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…H. sosnowskyi are rich in essential oils that contain mostly aliphatic esters, with the organic compound octal acetate or octyl ethanoate (molecular formula C 10 H 20 O 2 ) as the main constituent [ 20 ]. The substances present in these essential oils have strong, biologically active potential [ 20 ]. Although throughout Europe’s history, people have believed that the primary hazardous components of hogweeds were various coumarins (a vanilla-scented compound) [ 21 , 22 , 23 ], an article by Jakubska-Busse et al (2013) investigated H. sosnowskyi and Heracleum mantegazzianum and showed that they contain many additional toxic components.…”
Section: Methodsmentioning
confidence: 99%